Comparison of Left Ventricular Systolic Function by 2D Echocardiography between Diabetic and Non-Diabetic Patients undergoing Percutaneous Coronary Intervention in Non-ST elevated Myocardial Infarction - Chowdhury, MSI Tipu; Hoque, Harisul; Mahmood, Manzoor; Ahmed, Khurshed; Rahman, Md Mukhlesur; Khaled, Fakhrul Islam; Md Iqbal, Khaled; Gachchhader, Pritam Kumar; Fatema, Nilufar; Zaman, SM Mustafa (University Heart Journal, 2019)
Background: Long term mortality is higher in patients with Non-ST-segment elevated myocardial infarction (NSTEMI) than those with STEMI. In diabetic patients with NSTEMI are at high risk for subsequent cardiovascular events. But, the widespread use of drug eluting stents(DES) will further improve outcomes in patients with diabetes undergoing early percutaneous coronary intervention(PCI). Objective: The aim of the study was to determine the changes in left ventricular (LV) systolic function after successful PCI in NSTEMI diabetic patients compared with non-diabetic patients. Methods: From April 2017 to March 2018, this comparative clinical study was carried out in the Department of Cardiology, University Cardiac Center, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. 30 diabetic and 34 nondiabetic patients with NSTEMI undergoing Percutaneous coronary intervention were included in the study. Successful PCI with drug eluting stent was performed for all patients. 2-Dimensional echocardiography was done at baseline, at discharge following PCI and 3 months thereafter to measure the LV systolic functions and compare them between diabetics and non-diabetics at all levels of evaluation to assess the outcome of intervention. Results: At baseline LVEF was somewhat lower in diabetic group than that in non-diabetic group. Number of segments with abnormal wall motion (WMA) was higher in the diabetics compared to the non-diabetics. While the LVEDV, LVIDd and LVIDs were significantly greater in the former group than those in the latter group, the LVESV was no different between the groups. At discharge, no significant improvement was observed in either group following PCI in terms of LVEF, number of segments with WMA, LVIDd and LVIDs. However, both LVEDV and LVESV reduced effectively in both groups with decrease of LVESV being more marked in the nondiabetics compared to that in diabetics (p = 0.018). However, 3 months after PCI, LVEF improved 8.4±1.2% in diabetics and 7.9±1.2% in non diabetics but the difference of this improvement between two groups was not statistically significant(p = 0.631). Similarly baseline to 3 months after PCI LVIDs decreases in diabetics 5.7±1.9% and in non diabetics 4.8±1.1% but the difference between these two groups was not significant (p = 0.201). Diabetic patients more often required 2 stents (p = 0.30), although the diameter and length of the stents did not differ between the study groups. Conclusion: Our study demonstrated that improvement of the parameters of left ventricular systolic function after using of drug eluting stent in diabetic patients with NSTEMI was not inferior to the non diabetic group under same condition. So, indications of PCI with drug eluting stent may be extended in diabetic patient with NSTEMI. University Heart Journal Vol. 14, No. 2, Jul 2018; 47-52